2022
DOI: 10.4041/kjod21.248
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of artificial intelligence-assisted landmark identification in serial lateral cephalograms of Class III patients who underwent orthodontic treatment and two-jaw orthognathic surgery

Abstract: Objective: To investigate the pattern of accuracy change in artificial intelligence-assisted landmark identification (LI) using a convolutional neural network (CNN) algorithm in serial lateral cephalograms (Lat-cephs) of Class III (C-III) patients who underwent twojaw orthognathic surgery. Methods: A total of 3,188 Lat-cephs of C-III patients were allocated into the training and validation sets (3,004 Lat-cephs of 751 patients) and test set (184 Lat-cephs of 46 patients; subdivided into the genioplasty and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Hong et al, the accuracy of AI-assisted cephalometric landmark detection in jaw orthognathic surgery cases had been reported to be 75%, even when orthodontic brackets, surgical plates, screws, fixed retainers, genioplasty, and bone remodeling were present [22]. A CNN model was 94.4% accurate for diagnosing orthognathic surgery cases using both lateral and frontal cephalograms [23].…”
Section: Orthognathic Surgeriesmentioning
confidence: 99%
“…Also, orthopedic treatments with skeletal anchorage are becoming a new paradigm for the early treatment of Class III malocclusion [49][50][51]. Several studies cite the use of extraoral apparatus associated with this type of anchorage [52,53].…”
Section: Vol 4 Suppl 2 Year 2023mentioning
confidence: 99%